Comparative Transcriptome Analysis of Mature Leaves of Dimocarpus longan cv. ‘Sijimi’ Provides Insight into Its Continuous-Flowering Trait - Shilian Huang; Xinmin Lv; Junbin Wei; Dongmei Han; Jianguang Li; Dongliang Guo (Horticulturae)
Longan (Dimocarpus longan Lour.) is an important tropical and subtropical fruit, and most of its cultivars bloom once a year (once-flowering, OF). Dimocarpus longan cv. ‘Sijimi’ (SJ) is a tropical ecotype variety that blooms several times a year (continuous-flowering, CF) without the need for low-temperature induction. Several studies have focused on the mechanism of continuous flowering in SJ longan; however, none used leaves as research material. As leaves are a key organ in sensing floral-induction signals, we compared gene-expression differences between mature leaves of CF (SJ) and OF (D. longan cv. ‘Shixia’ (SX) and D. longan cv. ‘Chuliang’ (CL)) longan by transcriptome sequencing. An average of 47,982,637, 43,833,340 and 54,441,291 clean reads were obtained for SJ, SX and CL respectively, and a total of 6745 differentially expressed genes (DEGs) were detected. Following Metabolic pathways, Plant-pathogen interaction and Biosynthesis of secondary metabolites, most of the other genes were assigned to the KEGG classifications of MAPK signaling pathway- plant, Plant hormone signal transduction, Amino sugar and nucleotide sugar metabolism and Starch and sucrose metabolism. WGCNA analysis clustered genes into 27 modules, among which bisque4 and darkorange2 module genes specifically were expressed at low and high levels in SJ, respectively. Different gene-expression patterns were detected between CF and OF longan in bisque4 and darkorange2 modules, especially the high levels of transcription factor (TF) expression and the large number of gibberellic acid (GA)-signaling-pathway-specific genes expressed at high levels in CF longan (SJ). Floral-induction-gene expression levels in CF longan, such as levels of GA-signaling-related and FT genes, were always high. In CF longan, after vegetative-growth accumulation, flowers could be directly induced, thereby eliminating the need for low-temperature induction.